Going international: the development and operations of al QaÃida in the Islamic Maghreb - Mangrem, Sarah Faye (AUC Knowledge Fountain, 2012)
Since 2006 there has been a uniquely independent and autonomous branch of al Qa’ida operating in the Sahel and Sahara region of North and West Africa. Relative to associated movements elsewhere, al Qa’ida in the Islamic Maghreb is geographically and financially isolated, dependent on its own members to mobilize both human and financial resources. Yet at this they have been particularly successful; smuggling contraband across African borders, kidnapping Europeans for ransom and playing middleman for Latin American cartels transporting huge amounts of drugs to Europe. The 2012 Tuareg rebellion and subsequent military coup in Mali has provided opportune timing as arms flood out of Libya, sold to the highest bidder at a time when al Qa’ida in the Islamic Maghreb is flush with cash. Using framing and resource mobilization theory, this thesis defines and contrasts this movement within larger context of al Qa’ida. It argues that, for the first time, we must discard laden and meaningless terms, and begin to understand al Qa’ida, and its affiliates as social movements, in order to understand both its past and possible future.